Teacher-Student Relationships In Sufi Schools In Central Asia - Ulugov Jasur Nasirdinovich (Zien Journals, 2026)
The article examines mentor–disciple relationships through the lens of Sufi traditions. In particular, it offers an in-depth philosophical analysis of the educational legacy found within the Yassavi, Kubrawi, and Naqshbandi orders that emerged in Central Asia. Within Sufism, the bond between mentor and disciple is understood not merely as a process of transmitting knowledge, but as a multifaceted practice grounded in spiritual and moral cultivation, ethical perfection, and inner purification.
Keywords: Dhikr; motivation; moral immunity; classical education